RESEARCH SCHOOLS AS ORGANIZATIONAL SYSTEM FOR TRAINING OF PHD STUDENTS - Boris I. Bednyi; Victor B. Kazantsev; Evgeny V. Chuprunov (Высшее образование в России)
The article presents an analysis of the general approaches to designing structured programs for the training of PhD students adopted by the European Union countries in the framework of the third cycle of the Bologna process. It is shown that research schools are aneffective organizational form to implement structured programs. Research schools are specializeduniversity structures created for training of researches in a particular subject area. Such schools should ensure close links between young scientists and major competitive research teams. Usingas a case in point the «Neurobiotechnologies» research school at the Lobachevsky State University of Nizhni Novgorod, we discuss a range of issues concerning the organization of postgraduate education, funding for dissertation research, networking and research staff mobility.